Fidaxomicin for the Treatment of Clostridioides difficile Infection in Adult Patients: An Update on Results from Randomized Controlled Trials - Daniele Roberto Giacobbe; Antonio Vena; Marco Falcone; Francesco Menichetti; Matteo Bassetti (MDPI AG, 2022)
In recently updated international guidelines, fidaxomicin is preferentially recommended as first-line treatment over vancomycin both for the first episode of CDI and for rCDI, based on the results of different randomized controlled trials (RCTs). Although noninferiority was the rule in phase-3 RCTs with regard to the primary endpoint of clinical cure, for shaping these recommendations, particular attention was devoted to the improved global cure and reduced risk of recurrent CDI (rCDI) observed with fidaxomicin compared to vancomycin in RCTs. Overall, while the major driver of choice should remain the global benefit for the patient, consideration of available resources should be necessarily weighed in the balance, since fidaxomicin still remains more costly than vancomycin. Against this background, precisely stratifying risk groups for rCDI will represent a crucial research trajectory of future real-life studies on the treatment of first CDI episodes. In the current narrative review, we discuss the updated evidence from RCTs on the efficacy of fidaxomicin for the treatment of either the first CDI episode or rCDI, which eventually supports its positioning within current treatment algorithms and guidelines.